Templets betydning i jødedommen på Jesu tid - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1984)
It is a widespread idea among students of ancient Judaism that the temple of Jerusalem in the post-exilic period gradually lost its religious and national significance and was replaced by the Torah, the Synagogue and a new spiritualized view of temple and worship. Bousset-Gressmann and R.E. Clements are well-known representatives of this hypothesis. It militates, however, against a great number of other sources bearing witness to the importance of the temple in the Greco-Roman period, especially as the driving force in Jewish revolts against the Seleucids and the Romans. In the article both temple-traditions are presented and analyzed with the aim of presenting a more adequate view of the temple which, at the same time, is able to account for both the temple-centered and the temple-critical traditions. The conclusion is that for Judaism as a whole the temple was the basic institution in the Greco-Roman period, playing as important a role as in the pre-exilic times. The temple-critical traditions are interpreted as supporting this conclusion as they are seen mainly as expressions of heretical groups – the Samaritans, the Qumran community and early Christianity – trying to re-interpret precisely the central symbol of Judaism – the temple.